Foods that cause adverse reactions and ailments: the EuroPrevall survey results in Vilnius (Lithuania) - Kavaliūnas, Andrius; Šurkienė, Genė; Dubakienė, Rūta; Stukas, Rimantas; Žagminas, Kęstutis (Acta medica Lituanica, 2013)
Aim. The aim of this study was to determine foods that cause adverse reactions and ailments to citizens of Vilnius (Lithuania). Methods. Vilnius University was a partner in the EuroPrevall integrated project – “The Prevalence Cost and Basis of Food Allergy in Europe”, which is a EU-funded multi-disciplinary research study. By implementing this project, 4 333 6–12 year old schoolchildren of the 1st–4th grades from primary schools in Vilnius were asked to answer an anonymous questionnaire (3 084 questionnaires were gathered in return, response rate 71.2%). Meanwhile, 3  985 adults were asked to answer similar questions during interviews (2 634 of them agreed to take part in the survey, response rate 66.1%). Results. Fruits and berries (24.6%), and mostly citrus fruits (7.8%) were the most common foods that caused clinical symptoms among the children. Other important problematic foods were milk and dairy (19.4%), chocolate (10.9%), egg (7.4%). Fruits and berries were also the most common foods that caused clinical symptoms among adults (33.3%); other important foods were nuts (19.6%), vegetables (11.8%), chocolate (9.8%). Meat, crustaceans, cereals were food that caused clinical symptoms least to children and adults (≤2.0%). Conclusions. The list of the most allergenic foods is different in various countries and regions. Food allergy is closely related with age, nutritional habits of the family and society, culture and religion. Therefore, we can find many similarities and disparities when comparing Vilnius with other cities or places in Europe and the world. In Lithuania, there are congenial conditions to grow and consume fruits, vegetables and dairy, therefore these foods are more likely to become allergens to some part of society.
Keywords: food; adverse reactions; hypersensitivity; food allergy